The sustainable production of Mediterranean cheeses. Highlights of the home-made cheeses from Sierra de Cádiz (Andalusia, Spain) - Navarro L.; Ruíz F.; Ruiz Avilés P. (Mediterranean livestock production: uncertainties and opportunities, 2008)
The production of goat and sheep milk cheeses in Sierra de Cádiz is an example of environmental and socioeconomic sustainable production, besides a relevant element of diversity, and rural development. The origin of the milk coming from autochthonous breeds; the extensive feeding system (Natural Parks of Grazalema and Alcornocales); and homemade production justify this assumption. In this paper, sustainable cheese production is explained, based on two surveys conducted among stockbreeders and cheese makers, besides interviews with local experts.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)